The Transcendent in the Cinematic Experience - Dimovski, Domen (Analiza: časopis za kritično misel, 2025)
Based on the theory of conceptual metaphors, we will introduce the idea of God and the divine as a concept, referring to how cinematic art depicts and treats spiritual or religious themes. In addition to mentioning traditional metaphors, we will focus on the idea of transcendence as an experience of transcending everyday perception and understanding of the world. We will explore the phenomenological relationship between immanence and transcendence, particularly in relation to how films attempt to depict the experience of ecstasy and otherness and to create experiences that transcend rational understanding. Since cinematic art does not depend solely on verbal expression but, to a large extent, on the sensual and emotional response of the viewer, it is of particular interest here because it manages to break through the boundaries of rational discourse and provide access to experiences usually associated with religion and spirituality. We will describe some possible strategies through which films evoke the meaning and sense of the transcendent in the living body of the viewer and examine how film becomes a means of expressing the ineffable – the (divine) reality that is beyond language.